2017
DOI: 10.1158/0008-5472.can-16-2568
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 Hypomorphic Missense Variants Confer Moderate Risks of Breast Cancer

Abstract: Breast cancer risks conferred by many germline missense variants in the BRCA1 and BRCA2 genes, often referred to as variants of uncertain significance (VUS), have not been established. In this study, associations between 19 BRCA1 and 33 BRCA2 missense substitution variants and breast cancer risk were investigated through a breast cancer case control study using genotyping data from 38 studies of predominantly European ancestry (41,890 cases and 41,607 controls) and nine studies of Asian ancestry (6,269 cases a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 36 publications
3
68
0
2
Order By: Relevance
“…According to a previous report by Shimelis et al , the c.7522G>A (p.Gly2508Ser) variant is associated with a moderate risk of breast cancer in Asian women (OR 2.68; p=0.004), which was comparable to our results. However, this result is not enough to provide a strong evidence (PS4) when applying the ACMG/AMP schemes 23. A functional assay did not fully support a deleterious effect of this variant on BRCA2 activity, suggesting the possibility that Asian population-specific genetic modifiers influenced the impact of the variant on the breast cancer risk 23.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to a previous report by Shimelis et al , the c.7522G>A (p.Gly2508Ser) variant is associated with a moderate risk of breast cancer in Asian women (OR 2.68; p=0.004), which was comparable to our results. However, this result is not enough to provide a strong evidence (PS4) when applying the ACMG/AMP schemes 23. A functional assay did not fully support a deleterious effect of this variant on BRCA2 activity, suggesting the possibility that Asian population-specific genetic modifiers influenced the impact of the variant on the breast cancer risk 23.…”
Section: Discussionmentioning
confidence: 93%
“…However, this result is not enough to provide a strong evidence (PS4) when applying the ACMG/AMP schemes 23. A functional assay did not fully support a deleterious effect of this variant on BRCA2 activity, suggesting the possibility that Asian population-specific genetic modifiers influenced the impact of the variant on the breast cancer risk 23. Ultimately, additional functional studies or larger population-based studies are required to further characterise this variant.…”
Section: Discussionmentioning
confidence: 96%
“…There is also evidence that some alleles confer a moderate risk of cancer. These can include hypomorphic variants in known “high‐risk” cancer syndrome genes (Shimelis et al., ; Spurdle et al., ), or clear loss‐of‐function alleles in other genes such as CHEK2 , PALB2 , and ATM (Couch et al., ). Low‐risk variants, largely identified by genome‐wide association studies, are usually common and cause subtle functional effects, such as small but significant changes in gene expression due to altered activity of proximal and distal regulatory elements (reviewed in Bogdanova, Helbig, & Dork, ; Ghoussaini, Pharoah, & Easton, ; Skol, Sasaki, & Onel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these rare missense substitutions in BRCA2 are explaining a similar fraction of ESCC as the protein truncating variants. The association of G2508S with ESCC risk should be interpreted with caution, as a functional study showed G2508S reduced activity with the homology‐directed repair assay, but had limited impact on its activity with the poly(ADP ribose) polymerase inhibitor assay and ssDNA binding activity . BRCA2 G2508S, interestingly, is not only associated with ESCC in Henan Chinese with high ORs, but also with moderate risk in breast cancer in the Asian population .…”
Section: Discussionmentioning
confidence: 99%